Possibilities of dry eye syndrome therapy in various types of ametropia - M. A. Kovalevskaya; V. B. Antonyan; M. I. Sergeeva (Российский офтальмологический журнал, 2023)
Purpose: to evaluate the impact of Optinol treatment on the ocular surface state in medical students with various types of ametropia.Material and methods. The study involved 3 groups of patients: two clinical groups and a control group. The first clinical group consisted of 34 students (68 eyes) with mild, moderate or high hyperopia, averagely aged 20.1 ± 0.5 years. The second clinical group consisted of 47 students (94 eyes) with mild, moderate or high myopia, average aged 20.6 ± 0.9 years. The control group was composed of 60 students (120 eyes), averagely aged 21.4 ± 1.2 years, with no ophthalmic pathologies. Each group received Optinol consecutively in three different formulations: Optinol® Gentle Repair: dexpanthenol 2 % and sodium hyaluronate 0.15 %, Optinol® Deep Hydration: sodium hyaluronate 0.4 %, Optinol® Express Moisturizer: sodium hyaluronate 0.21 %. The case histories of the patients and typical complaints were revealed by the questionnaire method. The state of the eyelids and the conjunctiva was assessed by biomicroscopy. To diagnose the dry eye syndrome (DES), special tests were used: LIPKOF, Schirmer and Norn tests.Results. Despite the higher LIPKOF scores in the 1st (hyperopic) group, showing stage III as compared to the 2nd (myopic) group where it scored stage I, the Norn test score showed a stronger reduction in the 2nd group. The LIPKOF test improved in the hyperopic group, falling to 1.23 ± 0.10 mm (stage I), which corresponded to one conjunctival fold. The index of tear film stability (Norn's test) increased in group 1 by 3.1 ± 0.1 sec, and in group 2 by 2.2 ± 0.2 sec.Conclusion. DES was found to be more frequent in hyperopic students. Optinol is a pathogenetically oriented drug, targeting tear production disorders and ocular surface changes. The drug demonstrates high efficacy, good tolerability and safety profile, so that it could be recommended for managing multiple types of ametropia.